ENHANCING FIRST GRADE STUDENTS READING COMPREHENSION SKILL OF MAN MALANG 1 ON NEWS ITEM TEXT THROUGH SKIMMING TECHNIQUE - Trisnian Ifianti (Journey: Journal of English Language and Pedagogy, 2018)
The point of this article is portraying how the ways Skimming Technique can enhance the primary review understudies' Reading Comprehension Skill on News Item Text at MAN Malang 1. In light of the preparatory study, the specialist found the classroom issues of this class particularly in perusing understanding ability on News Item Text of the primary evaluation understudies of MAN Malang 1. The students got trouble to grasp perusing writings which were given by the English educator. This trouble made 80% of the understudies of this class neglected to achieve the standard least of the school, which is 78.00 in their perusing understanding, and the normal score of this class was just 66.2. In this way, the understudies' perusing cognizance aptitude on News Item message must be moved forward. This study utilized Classroom Action Research (CAR) as the exploration outline. The subjects of this study were one class of the main evaluation understudies which comprised of 37 understudies. The systems of the study secured four stages: arranging, executing, perception, and reflection. The information accumulated was as quantitative and subjective information. The quantitative information was acquired from the perusing appreciation test, and the subjective information was gotten from the understudies perception and agenda and the field note of the educating and learning process.